Financial Leverage and its Determinants in Companies Producing Electricity from Wind Resources in Latvia - Bobinaite, Viktorija (Economics and Business, 2015)
The paper aims to analyse the development of the financial leverage and its determinants in companies producing electricity from wind resources in Latvia during 2005-2012. The financial ratio technique is used to compute the financial leverage in the companies and the regression analysis method is employed to determine the relationships between variables. The results of the analysis revealed that wind electricity generating companies use substantial share of debt and the financial leverage is increasing. Statistically significant relationships were found between the financial leverage and profitability of companies, their growth opportunities, collateral value of assets, size of the company and an effective tax rate. Results will be used to construct weighted average cost of capital (WACC) for the economic assessment of investment into wind electricity sector in Latvia.